2009
DOI: 10.1007/s10753-009-9139-x
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Forkhead Box A1 in Acute Lung Injury

Abstract: Abstract-Forkhead box protein A1 (FoxA1) is an evolutionarily conserved winged helix transcription factor with diverse regulatory functions. However, little is known about the role of FoxA1 in acute lung injury (ALI) and pulmonary cell injury. In this study, an in vivo model was employed whereby rats were administered an intravenous injection of oleic acid (OA, 0.1 ml/kg), and alveolar type II epithelial cells (AT-2 cells) injury was induced by hydrogen peroxide (H 2 O 2 ) in vitro. OA injection resulted in lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Specifically, it has been shown to play a pro-apoptotic role during oxidative-stress induced apoptosis in type II pneumocytes. 33 Over-expression of FOXA1 has been shown to promote apoptosis, 34 which has been implicated as a mechanism contributing to COPD and emphysema progression. 35 We demonstrate expression of FOXA1 protein in airway epithelium and lung parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has been shown to play a pro-apoptotic role during oxidative-stress induced apoptosis in type II pneumocytes. 33 Over-expression of FOXA1 has been shown to promote apoptosis, 34 which has been implicated as a mechanism contributing to COPD and emphysema progression. 35 We demonstrate expression of FOXA1 protein in airway epithelium and lung parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of Foxa1 also decreased the expression of lung differentiation markers [e.g. FOXA1 expression is increased in a rat model of ALI (acute lung injury), in which it is suggested to function in alveolar type II epithelial cell apoptosis [41], and is similarly necessary for H 2 O 2 -induced apoptosis in A549 cells [42]. This is at least partly due to the dependency of both CCSP (Scbg1a1) [35] and SP-B (Sftpb) [36,37] promoters on FOXA1 for activation in lung epithelium.…”
Section: Lungmentioning
confidence: 99%
“…FoXa1 is a member of the winged-helix family of transcription factors and shares structural similarities with FoXa2 and FoXa3. Song et al (14) reported that the overexpression of FoXa1 promoted pulmonary epithelial cell apoptosis in ali. Whether MalaT1 acts as a cerna for the mir-17-5p/FoXa1 axis, consequently regulating cell proliferation and apoptosis, in lPS-induced a549, remains unclear.…”
Section: Introductionmentioning
confidence: 99%